Composition and modification of the lung microbiome in patients with idiopathic pulmonary fibrosis - Victoria Maria Ruta; Teodora Gabriela Alexescu; Ana Rodica Ungur; Milena Adina Man; Victoria Georgiana Sfirlea; Iulia Olimpia Pfingstgraf; Nicoleta Motoc; Carmen Monica Pop (Journal of Mind and Medical Sciences)
Lungs have long been considered sterile, but recent research has shown that a large number of microbiological organisms exist in the lungs of healthy subjects (including bacteria, fungi, and viruses), collectively known as the microbiome. It undergoes changes in patients with respiratory pathology. Studies in idiopathic pulmonary fibrosis show that a large number of bacteria or the abundant presence of potentially pathogenic bacteria can cause disease progression and exacerbation, and can implicitly increase mortality. There seems to be a quantitative balance, a well-established proportion between the components of this microbiome, which is disturbed during a disease and can reach a "state of pulmonary dysbiosis". Evidence suggests that the microbiome may be used as a prognostic biomarker and may also explain the pathogenesis of interstitial fibrosis.